Beware of FDI statistics! - Karl P. Sauvant (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2017)
FDI statistics have a number of serious shortcomings that limit their accuracy, and therefore also their usefulness for analysis. This Perspective identifies five shortcomings whose correction should be prioritized and provides advice on how to do so.
Keywords: 330